The Prison Library as Sanctuary : Using a Whole-Person Approach in Prison Libraries to Support Mental and Emotional Health in Incarcerated Women - Bultena, Camille (Pathfinder: A Canadian Journal for Information Science Students and Early Career Professionals, 2025)
Prison library services in both federal and provincial correctional institutions across Canada are inconsistent, largely underfunded and understaffed. There is limited data around current prison library services which impacts the ability to plan future correctional library services. This research is intended to identify this information gap and aid in future modeling of correctional library services. This research will also examine how libraries can employ a holistic framework to support the mental health and wellbeing of women experiencing incarceration. Additionally, this paper will explore how prison libraries can be decolonial spaces within a carceral context, to act in part as vehicles of reconciliation and attempt to uniquely address the gross over-representation of Indigenous peoples in the Canadian justice system. Through employing a holistic framework and offering library spaces and services that support mental health and emotional health, prison libraries have the potential to transform lives and in a small way pursue reconciliation.